2013
DOI: 10.1002/etc.2180
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of ZnO nanoparticles to the copepod Acartia tonsa, exposed through a phytoplankton diet

Abstract: Zinc oxide (ZnO) nanoparticles are being increasingly utilized in a variety of products and applications and are therefore commonly discharged into aquatic environments, increasing exposure and potentially impacting aquatic organisms. Zinc oxide nanoparticles can depress growth of some marine phytoplankton, and several examples of nanoparticle trophic transfer have been documented, although not within planktonic communities. The authors test whether feeding on ZnO-exposed phytoplankton could cause toxic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…However, an exposure of the copepod Acartia tonsa to ZnO-NP-dosed diatom T. weissflogii at the highest concentration of 263 mg L À1 Zn showed a significant reduction in survival and reproduction by 52 % and 50 %, respectively, after 7 days of exposure [29]. These authors confirmed the transfer of ZnO-NPs to A. tonsa from the dosed algae, illustrating their potential for trophic transfer [29].…”
supporting
confidence: 66%
See 1 more Smart Citation
“…However, an exposure of the copepod Acartia tonsa to ZnO-NP-dosed diatom T. weissflogii at the highest concentration of 263 mg L À1 Zn showed a significant reduction in survival and reproduction by 52 % and 50 %, respectively, after 7 days of exposure [29]. These authors confirmed the transfer of ZnO-NPs to A. tonsa from the dosed algae, illustrating their potential for trophic transfer [29].…”
supporting
confidence: 66%
“…Toxic effects of ZnO-NPs to these small crustacean species are associated with the primary particle size, the concentration of free zinc ions, and the aggregates of the ZnO-NPs. More importantly, some studies reported that toxic effects of ZnO-NPs may also be occurring at environmentally realistic concentrations [29,31].…”
mentioning
confidence: 99%
“…92, 93 Environmental factors are examined, including how ENMs interactively affect soil water availability 94 and soil bacterial communities. 95 Single-species experiments that assess ENM bio-association 96, 97 or bioaccumulation 71, 98 precede and motivate using microcosms for assessing dual species trophic transfer 98-101 and potential biomagnification. 102 …”
Section: What Exposure Conditions Are Used In Assessing Enm Ecologicamentioning
confidence: 99%
“…To the best of our knowledge, few studies investigated the non-target effects of nanoparticles against predatory copepods (Oberdorster et al 2006;Jarvis et al 2013;Park et al 2014, see Fabrega et al 2011, and Baun et al 2008 for reviews), and no evidences are available about the toxicity of green-synthesized nanoparticles against these predaceous aquatic organisms. No efforts have been carried out to integrate classic biological control programs and nanobiotechnological tools for eco-friendly control of mosquito vectors.…”
Section: Introductionmentioning
confidence: 97%